All’ombra dell’istituzione totale. La «sociologia pubblica» alla prova del penitenziario - Andrea Borghini (Cambio)
The contribution aims to reflect on the emancipatory role that sociology can play, in its public dimension, when confronted with a total institution, such as the penitentiary. The historical-critical assumptions from which the reflection moves can be traced, on the one hand, to those values of inclusion and social justice to which public sociology, in the ‘version’ that Burawoy (re)launched in 2004, looks to as inalienable ethical principles. And which, notoriously, due to the type of inmate population in penal institutions (Italian and otherwise) and the history of the penitentiary itself, are often disregarded and ignored. On the other hand, it seems more interesting than ever to test the liberating capacity of sociology in a ‘public’ institution such as the prison, in comparison with a ‘public’ with peculiar characteristics, which only partially reflects that notion of organic public that has become increasingly central in Burawoy’s conception. This ‘social experiment’ will be conducted from a particularly interesting case study, namely the project of university prison centres, which constitute a virtuous encounter between university culture and the prison world. Specifically, the group under investigation will be inmates enrolled in university courses. Through this case study, it will be possible to verify the limits and possibilities of a sociological style, which turns out to be sociology in its public version, which represents, in an era of strong social inequalities and urgent global issues, a valuable tool to give voice and centrality to sociology, to its critical demands and, through of it, try to listen to the ‘cry of pain’ coming from a growing part of the men and women of our world.